Surgical management of chondromyxoid fibroma at meta-diaphyseal junction of proximal tibia: a case report - Shivanna, Umesh M.; Nagaraj, Nishank C.; Venkataramana, Karthik M. (International Journal of Research in Orthopaedics, 2025)
Chondromyxoid fibroma (CMF) is a rare, benign tumour of the bone. It represents less than 1% of all bone tumours. We present a case of a 20-year-old female who came with chief complaints of pain and swelling in right leg for 3 months. Radiograph showed features suggestive of large multiloculated osteolytic, radiolucent lesion with thinned out cortices in right proximal tibia. MRI showed exophytic lesion and features suggestive of osteosarcoma. USG guided biopsy reported as chondromyxoid fibroma. Patient underwent curettage of tumour followed by reconstruction with allograft and stabilized with internal fixation. Final histopathological report showed features suggestive of chondromyxoid fibroma. Patient made uneventful recovery with no signs of recurrence and good functional range of motion (ROM) of the knee joint after 2 years of follow up. Histopathology is the gold standard and mandatory for confirmation of the diagnosis. Curettage and filling the defect with polymethyl methacrylate (PMMA) or bone graft is the mainstay treatment of choice.